A educação e a legislação brasileira no enfrentamento da violência sexual contra crianças e adolescentes - Silva, Elivânia Lima da (2022)
The present study dealt with education and Brazilian legislation in the last two decades, seeking to analyze the preventive measures adopted in the context of education to combat sexual violence against children and adolescents. Sexual violence is a social phenomenon that permeates all society (national and international) affecting children and adolescents at ali stages oflife.It is a violation ofhuman and sexual dignity that causes various physical, psychological and social problems, both in victims and in their fam.ilies and even in society in general. It is a form of violence that causes social repudiation and despite the advance in the protective legal framework aimed at confronting it, it is still very present in Brazilian society. Masked by the ''pact of silence" that contributes to underreporting, the prolonged time of its occurrence worsening the healthy development of thousands of children and adolescents in the national territory. In this sense, Brazil has invested in public policies to control and eradicate cases of this nature, especially since the implementation ofthe National Planto Combat Sexual Violence Against Children and Adolescents, in 2000. In this context, education has among its objectives the obligation to prepare their students for life in society, based on formative and informative elements capable of ensuring the full development of ali. Still, the school is the second place where children and adolescents spend most of their time, therefore, it assumes a prominent place in the social protection network, conducive to the behavioral monitoring of school subjects and the identification of suspected cases of sexual violations. This is an exploratory qualitative research. The collection instrument used was document analysis (plans, programs, projects and legislation). The content analysis technique was the basis for the analysis of the collected material and the construction of inferences. The focus of the study on the problem of sexual violence against children and adolescents and the process of confrontation based on education and legislation point to a change in the paradigm of accountability, attributing it to the family, the State and society, with a focus on a guaranteeing legislation that demarcates children and adolescents as subjects of rights from the promulgation of the Federal Constitution of 1988. The legislative changes evidence a social mobilization resulting from the process of redemocratization the country. However, the study points to timid results in public coping policies. Education is seen as important equipment for the prevention, identification and referral of cases of this nature, it lacks initial and continuous training of professionals with a view to promoting the empowerment of children and adolescents, encouraging them to report cases of abuse or exploitation who experience or have knowledge, from the dissemination ofknowledge.